Assessing veterinarians’ perspectives of anatomy education and the effect of supplemental resources on student learning - Hansen, Chandler Elizabeth (Kansas State University, 2024)
Gross anatomy is usually one of the first courses encountered by veterinary students in professional school as it lays a foundation of knowledge that is to be built upon. Veterinarians use anatomy in diagnoses, surgery, physical exams, treatment planning, communication, and more. Undergraduate students must complete various prerequisite courses as minimum preparation for a professional program and curriculum; however, anatomy is typically not a required prerequisite. Consequently, anatomy poses academic challenges due to the prevalence of Latin or Greek anatomical terms, alongside the extensive and detailed course content that covers multiple species and their anatomical variations. Additionally, anatomy education is increasingly focusing on competency-based learning and transitioning to more technologically focused teaching methods. For these reasons, this dissertation seeks to address the question, “How can veterinary anatomy instruction be improved to enhance student retention, reduce cognitive load, and improve clinical relevance?” To address these challenges, this dissertation explores the development of two supplemental resources and an alumni perception survey to improve veterinary anatomy education. First, pre-laboratory videos were created to provide students a synopsis of lab assignments, allowing deeper engagement and reducing cognitive overload. By using visual and auditory elements, these videos facilitate better understanding of complex anatomical concepts. Second, a novel winter-break pre-course was designed to aid the transition from canine to ungulate anatomy. This resource builds upon prior knowledge, offering preparatory material to ease cognitive strain during the transition between canine and ungulate anatomy. Lastly, in response to the shift towards competency-based curricula in many veterinary schools, the third project gathered alumni perceptions of their veterinary anatomy education. These findings help ensure that present curricula adequately prepare graduates for real-world veterinary practice. Alumni perceptions may be used to adjust teaching methods or assist with the creation of additional innovative resources to further prepare graduates for clinical application. In conclusion, this dissertation proposes novel, online resources to improve veterinary anatomy education, including pre-laboratory videos and a winter-break pre-course designed to better equip students for classroom learning. Additionally, by incorporating alumni feedback, this work ensures ongoing enhancement of teaching methods to better prepare veterinary graduates for real-world practice.
Keywords: Anatomy; Teaching; Learning; Education; Veterinary